Extraintestinal Manifestations and Other Comorbidities in Ulcerative Colitis and Crohn Disease: A Danish Nationwide Registry Study 2003–2016. Issue 3 (25th August 2020) - Vadstrup, Kasper; Alulis, Sarah; Borsi, Andras; Jørgensen, Tine Rikke; Nielsen, Agnete; Munkholm, Pia; Qvist, Niels
Abstract: Background: Extraintestinal manifestations (EIMs) in inflammatory bowel disease (IBD) may be a frequent complication to an underlying abnormal immune response. This study investigated the occurrence of EIMs in Crohn disease (CD) and ulcerative colitis (UC) patients using population-based data in Denmark from 2003 to 2016. Methods: In this national registry-based study, incident CD and UC patients between 2003 and 2015 were matched on age and gender with non-IBD controls and followed until 2016. The selected EIMs for this study included 51 different diagnoses divided into biological systems of diseases, which were tested for differences in the timing and occurrence of EIMs. Results: The study cohort included 10, 302 patients with CD and 22, 144 patients with UC. The highest risk of patients experiencing EIM/comorbidities for the first time before their IBD diagnosis was in the skin and intestinal tract systems. For CD, the odds ratio of having an EIM before or after IBD diagnosis, as compared with controls, was significant in the skin, intestinal tract, hepatopancreatobiliary, musculoskeletal, ocular, renal, and respiratory systems. For UC, the risks were similar before and after UC diagnosis, apart from the nervous system where the odds ratio was significantly higher before the diagnosis of UC, and significantly lower after diagnosis for diseases in the ocular system. Conclusions: EIMs in CD and UC patients may also precede their IBD diagnosis. These findings may indicate a significant diagnostic delay of CD and UC, and the occurrence of known EIMs should prompt physicians to look for patients possibly having underlying IBD. Lay Summary: Extraintestinal manifestation (EIM) in inflammatory bowel disease (IBD) may be a frequent complication to an underlying abnormal immune response. This study implicates EIMs in Crohn disease (CD) and ulcerative colitis (UC) patients may precede their IBD diagnosis and this may indicate a significant diagnostic delay of CD and UC.